Development of Photodynamic Antimicrobial Chemotherapy (PACT) for Clostridium difficile. - Luisa De Sordi; M Adil Butt; Hayley Pye; Darina Kohoutova; Charles A Mosse; Gokhan Yahioglu; Ioanna Stamati; Mahendra Deonarain; Sinan Battah; Derren Ready; Elaine Allan; Peter Mullany; et al. (PLoS ONE, 2015)
Clostridium difficile is the leading cause of antibiotic-associated diarrhoea and pseudo membranous colitis in the developed world. The aim of this study was to explore whether Photodynamic Antimicrobial Chemotherapy (PACT) could be used as a novel approach to treating C. difficile infections.PACT utilises the ability of light-activated photosensitisers (PS) to produce reactive oxygen species (ROS) such as free radical species and singlet oxygen, which are lethal to cells. We screened thirteen PS against C. difficile planktonic cells, biofilm and germinating spores in vitro, and cytotoxicity of effective compounds was tested on the colorectal adenocarcinoma cell-line HT-29.Three PS were able to kill 99.9% of bacteria in both aerobic and anaerobic conditions, both in the planktonic state and in a biofilm, after exposure to red laser light (0.2 J/cm2) without harming model colon cells. The applicability of PACT to eradicate C. difficile germinative spores indirectly was also shown, by first inducing germination with the bile salt taurocholate, followed by PACT.This innovative and simple approach offers the prospect of a new antimicrobial therapy using light to treat C. difficile infection of the colon.